Intracranial meningiomas: clinical, intrascopic and pathomorphological causes of recurrence (literature review) - K. K. Kukanov; O. M. Vorobyova; Yu. M. Zabrodskaya; E. G. Potemkina; V. V. Ushanov; M. M. Tastanbekov; N. E. Ivanova (Сибирский онкологический журнал)
Introduction. Meningiomas are the second most common central nervous system (CNS) tumors in adults. most meningiomas are benign tumors. Anaplastic and atypical meningiomas account for 25% and have a high recurrence rate even after radical tumor resection and radiotherapy. The prognosis of patients with anaplastic meningiomas remains disappointing; most of them die within the first 2 to 5 years after surgery. Purpose: to discuss the challenges in diagnosis and treatment of recurrent meningiomas, to identify the causes of tumor progression, and to assess the clinical features and radiographic findings as well as specific pathomorphological and molecular genetic characteristics. material and methods. We searched for publications in the Pubmed, EMBASE, Cohrane Library and eLibrary databases published between January 2000 and January 2019 on the issue of recurrent intracranial meningiomas, in particular atypical and anaplastic meningiomas. Results. The review systematizes data on the prognostic factors for survival, relapse-free period, and disease progression. particular attention was paid to the radical resection of the tumor and the assessment of the grade of anaplasia. The current data on radiotherapy and drug therapy were presented.  the controversial issues of approaches to the assessment of morphological prognostic criteria were discussed. The current knowledge on the most common genetic mutations in meningiomas, the prospects for their study and use for targeted therapy were presented. Conclusion. The management of meningioma still presents some unresolved issues.  There are no optimal standards for diagnosis and treatment of patients with meningiomas that would take into account biological characteristics, including growth characteristics and molecular genetic profile. There are no clear prognostic criteria for recurrence and continuity in further management after surgical treatment, which affects the mortality rate and quality of life in this category of patients. New fundamental data that will determine a different strategy in the treatment of intracranial meningiomas are needed.